Alternative energy sources geothermal, water & wind - Films for the Humanities (Firm) (Westlake Village, CA: Silvermine Video, 2008)
The need for energy is as old as humankind. From the dawn of civilization, people have been searching for new and more efficient sources of energy to cook their food and provide their shelter with heat and light. Some of the most recent areas of exploration in the ongoing search for new energy sources have, in fact, been available to us from the beginning of time : The wind, the water and geothermal energy, utilizing the heat from the core of the planet. In this comprehensive and informative presentation, methods for the derivation of energy from some of these lesser publicized energy sources are discussed, covering aspects from how they work, the history of their exploitation, relative shortcomings and advantages, and their future potential. The use of windmills, from ancient to modern times is covered with emphasis placed on the need to supplement this erratic energy source to increase their effectiveness. In the area of water power, the use of tidal power, wave energy , and the energy to be derived from kelp farms are elaborated upon. with emphasis on their value in terms of a expendables energy source. Finally, geothermal energy sources, especially progress made in the twentieth century in harvesting our planet's heat, is discussed. Special mention is made of the worldwide availability as well as its successful utilization around the world today- cover.
DVD.
Keywords: Renewable energy sources; Geothermal resources; Water-power.; Wind power